A Systematic Review on Caregiver’s Burden Among Caregivers of Dementia Patients in Malaysia - Nuurain Amirah Mohd Razi; Halimatus Sakdiah Minhat; Nor Afiah Mohd Zulkefli; Norliza Ahmad; Tengku Amatullah Madeehah Tengku Mohd; Hafiz Jaafar (Malaysian Journal of Medicine and Health Sciences, 2024)
Indexed by Scopus/MyCite